Development of polymorphic simple sequence repeat markers in Huperzia serrata (Lycopodiaceae) - Bin Guo (Applications in Plant Sciences, 2019)
Premise The natural population size of Huperzia serrata (Lycopodiaceae) has dramatically decreased and the species has become endangered due to overexploitation. Here, we developed simple sequence repeat (SSR) markers for H. serrata to survey both its genetic diversity and population structure. Methods and Results Based on 177 individuals, 120 SSR primer pairs were developed and optimized from five regions of the H. serrata transcriptomic data. Of these primer pairs, 20 were successfully amplified and 10 showed obvious polymorphism. These polymorphic loci were investigated to study the genetic diversity of H. serrata. Two to 11 alleles per locus were identified, the level of observed heterozygosity ranged from 0.00 to 1.00, and the level of expected heterozygosity ranged from 0.19 to 0.79. All loci were successfully amplified in H. crispata, H. sutchueniana, and H. selago. Conclusions The 10 polymorphic primer pairs developed here will be valuable for studies of the endangered H. serrata and other related species.